Knowledge, Attitudes and Behaviors of Society Towards Blood Donation in Turkey (Turkey Health Literacy Journal, 2021)
Blood and blood products are vital biological products. Understanding the level of knowledge, attitude and behavior of society towards blood donation is of great importance to obtain the blood and blood product needed at the national level in a healthy and safe way. In this study, by compiling published studies on awareness, attitudes and behavior of the various groups of society in Turkey towards the blood donation; it is aimed to understand the motivation factors related to blood donation in the society, to determine obstacles and to review what can be done to improve the health of the society by increasing the number of volunteer blood donors and providing safe blood supply.